1954
DOI: 10.3181/00379727-86-21124
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid in Two Patients with Wilson's Disease (Hepatolenticular Degeneration).

Abstract: In the course of a complete laboratory examination of a brother and sister both suffering from Wilson's disease, it was discovered that the serum urate levels in both individuals were unusually low ( 1-2 rng %), according to the colorimetric method ( 1 ) . To elucidate the mechanism of this behavior it was decided to determine uric acid pool size and turnover rate by injecting W5 uric acid in the manner previously described ( 2 ) .The male subject was injected intravenously with 2 1.7 mg of N15 uric acid (14.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1957
1957
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, renal glycosuria was also observed in half of the patients. Additionally, WD patients frequently exhibit hypouricemia [ 30 , 31 ]. Significant low-weight proteinuria was also noted in 25% of 40 patients in Sözeri's report, mostly in patients with no or short duration of treatment [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, renal glycosuria was also observed in half of the patients. Additionally, WD patients frequently exhibit hypouricemia [ 30 , 31 ]. Significant low-weight proteinuria was also noted in 25% of 40 patients in Sözeri's report, mostly in patients with no or short duration of treatment [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreased reabsorption of filtered urate with increase of urate clearance is found in many generalized proximal tubular disorders, e.g. in the Fanconi syndrome (Sirota et al 1952), Wilson's disease (Bishop et al 1954), and in cadmium poisoning (Kazantzis et al 1963). The clearance is only slightly below that of inulin, and is not appreciably altered after administration of uricosuric drugs.…”
Section: Abnormalities Of Urate Excretionmentioning
confidence: 99%
“…Early studies demonstrated excessive urinary excretion of copper, and renal damage was attributed to the deleterious effect of accumulation of copper in the kidneys, resulting into progressive deterioration of tubular functions and also renal plasma flow and glomerular filtration rate, similar to the effects of other heavy metals. Renal tubular dysfunction with consequent aminoaciduria, hypercalciuria and hyperphosphaturia inducing nephrocalcinosis, uricosuria with decreased serum urate level, nephrolithiasis, glucosuria in the absence of hyperglucemia, hypokalaemia and renal tubular acidosis are documented [9,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%